TRANSACTIONS ON LAND AND APARTMENTS RIGHTS: BETWEEN BUSINESS PRACTICE FACTS AND ADAT NORMS - Joesoef, Iwan Erar (Jurnal Yuridis, 2025)
The objective of this research was to study the business practices on Land and Apartment Rights of which refer to Western Law whilst the Indonesia Land Law including Apartment Law based on Adat Law. The transaction is running expeditiously in business community. Refer to Apartment Law in Indonesia, the transaction of which based on Adat Law. The conception stated that land rights transaction is "terang, riil dan tunai" ("transparent, real and cash") it means that the transaction should be in cash, real and delivery in front of Land Deed Officer_Pejabat Pembuat Akta Tanah (PPAT). The legal problem is how the developer can sell the Apartement ("strata title") to the consumer with pre-payment (indent) of which the Apartment not yet construct or under construction or in planning. The result of this research is that the developer sold the Apartment by Pre-Project Selling of which the Bank Institution ask the Developer the Buy Back Guarantee. The method of this research is legal document study. The conclusion of this research is the transaction should be in front of Notary Public by issuing a fair Pre-Agreement (Perjanjian Pengikatan Jual Beli_PPJB).